Overexpression of the GR Riborepressor LncRNA GAS5 Results in Poor Treatment Response and Early Relapse in Childhood B-ALL - Xagorari, M.; Marmarinos, A.; Kossiva, L.; Baka, M.; Doganis, D.; Servitzoglou, M; Tsolia, M.; Scorilas, A.; Avgeris, M.; Gourgiotis, D. (Cancers, 2021)
Glucocorticoids (GCs) remain the cornerstone of childhood acute lymphoblastic leukemia (chALL) therapy, exerting their cytotoxic effects through binding and activating of the glucocorticoid receptor (GR). GAS5 lncRNA acts as a potent riborepressor of GR transcriptional activity, and thus targeting GAS5 in GC-treated chALL could provide further insights into GC resistance and support personalized treatment decisions. Herein, to study the clinical utility of GAS5 in chALL prognosis and chemotherapy response, GAS5 expression was quantified by RT-qPCR in bone marrow samples of chB-ALL patients at diagnosis (n = 164) and at end-of-induction (n = 109), treated with ALL-BFM protocol. Patients' relapse and death were used as clinical end-points for survival analysis. Bootstrap analysis was performed for internal validation, and decision curve analysis assessed the clinical net benefit for chALL prognosis. Our findings demonstrated the elevated GAS5 levels in blasts of chALL patients compared to controls and the significantly higher risk for short-term relapse and poor treatment outcome of patients overexpressing GAS5, independently of their clinicopathological data. The unfavorable prognostic value of GAS5 overexpression was strongly validated in the high-risk/stem-cell transplantation subgroup. Finally, multivariate models incorporating GAS5 levels resulted in superior risk stratification and clinical benefit for chALL prognostication, supporting personalized prognosis and precision medicine decisions in chALL.